Evaluation of early trabecular changes around implants using fractal analysis and panoramic indices - Mert Keles; Ibrahim Burak Yuksel; Dilek Ozkan Sen; Omer Ogutcen; Muhammet Emin Arslan; Fatma Ucan Yarkac; Osman Babayigit (PLoS ONE, 2026)
Early trabecular changes around dental implants may not be adequately captured by conventional panoramic morphometric indices. Fractal analysis has been proposed as a quantitative method for detecting subtle changes in bone microarchitecture. This study aimed to evaluate early peri-implant trabecular structural changes using fractal analysis and panoramic morphometric indices during the unloaded healing period. This retrospective study included 60 single-tooth dental implants. Standardized panoramic radiographs were obtained at baseline and 3 months postoperatively. Mandibular cortical width, panoramic mandibular index, and fractal dimension values were measured in mesial, distal, and apical regions using ImageJ software. As all implants healed submerged and unloaded, periodontal parameters—plaque index, gingival index, bleeding on probing, and probing pocket depth—were recorded from natural teeth in the same quadrant. Baseline and 3-month values were compared using paired t-tests, with statistical significance set at p < 0.05. Fractal dimension values increased significantly in all evaluated regions at 3 months compared with baseline (p < 0.05), indicating measurable early trabecular structural changes. In contrast, mandibular cortical width and panoramic mandibular index showed no significant changes. Among periodontal parameters, only gingival index demonstrated a significant improvement (p < 0.001), reflecting reduced gingival inflammation. Fractal analysis detected early trabecular changes during the 3-month unloaded healing period, whereas conventional panoramic morphometric indices showed no significant change. These findings should be interpreted as indicators of trabecular reorganization rather than direct evidence of osseointegration. Fractal analysis may provide supplementary, non-invasive information during early radiographic follow-up.